Design and Synthesis of Organic Molecules as Antineoplastic Agents - Boga, Carla; Micheletti, Gabriele (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of Special Issue articles with a multidisciplinary character, linking biology, medicine, and synthetic organic chemistry. The synthesis and full characterization of about 180 novel organic species, both of natural and synthetic origin, often designed with the support of in-silico studies, are set out in the book. In several articles, molecular hybridization approaches have been used as a successful multi-target strategy for the design and development of novel antitumor agents. Rigorous and careful biochemical studies ranging from in-vitro experiments on a plethora of human-cancer derived cell lines to in-vivo and ex-vivo studies allowed the authors to identify the molecular targets and gain useful information on structure-activity relationships (SAR). For this reason, this collection should interest many readers from different scientific fields.